Poverty is multidimensional: But do we really need a multidimensional poverty index? - Jose Ramon G. Albert; Jana Flor V. Vizmanos (Philippine Institute for Development Studies (PIDS), 2018)
The Philippines, just like many other developing countries, has measured poverty using one-dimensional monetary-based indicators, although poverty is multidimensional in nature. Various work on generating a multidimensional poverty index (MPI) has been undertaken using data from several countries, including that done by the United Nations Development Programme with the Oxford Poverty and Human Development Initiative. Several studies have also used national data for generating an MPI. The measurement of multidimensional poverty in the Philippines should depend on a careful investigation on whether there is much value added in producing a composite index of poverty. Just because poverty is multi-dimensional need not mean that its measurement should be. This study examines discusses various issues regarding the production of a MPI, from the choice of the underlying indicators for the index, the weights assigned to the indicators, as well as the aggregation process. It also reviews measurements on quality of life (happiness and well-being), on poverty and welfare (including multidimensional poverty) and on sustainable development. It examines various possibilities of an MPI for the Philippines based on several waves of household surveys (viz., the National Demographic and Health Survey, the Annual Poverty Indicator Survey, and the Family Income and Expenditure Survey) and several approaches on choices of indicators and weights. This paper also looks at the robustness of trends in the resulting MPI approaches, and some policy issues attendant to the measurement of multidimensional poverty, especially on its relationship with traditional income poverty measurement.
Keywords: 330; multidimensional poverty; composite index; indicators; weights; aggregation